Using economic indicators to improve investment analysis - Tainer, Evelina M. (J. Wiley& Sons, 2006)
This book is an indispensable resource for anyone that wants a practical understanding of the economy and how it is measured. The information is clear, concise, and will help investors at all levels leverage the vast amount of economic data available